LEARNING REFLECTION ON BASIC MATHEMATICAL SUBJECT IN HIGHER EDUCATION AS THE FINAL STAGE OF LESSON STUDY IMPLEMENTATION - Martyana Prihaswati; Eko Andy Purnomo; Sukestiyarno Sukestiyarno; Mulyono Mulyono (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Students often have math anxiety which results in low learning outcomes. Giving story questions turned out to raise student’s difficulties in solving problems, including identif ying elements that are known, asked, andadequacy of elements, and making mathematical models of story problems. This indicates that the problemsolving ability of non-mathematics major students in basic mathematics courses is low. Lesson Study Learning based on character education can facilitate the acquisition of solutions to the above problems. The most important stages in lesson study are stages of reflection (see), in which the stages are stated all findings in learning are then given input in order to improve learning. This study uses the descriptive method with a qualitative approach. The activity carried out is to describe the reflection of basic mathematics learning as the final stage of the lesson study implementation. The research variable is in the form of a dependent variable, such as students' problem solving abilities and independent variables, namely student activity and creativity. It was obtained an average problem solving ability of 81.52. While the students’ activeness with an average of 8 3.4 categories is very active and the average of students’ creativity is 81.3 with a very good category. The character building for students, such as honesty, discipline, creativity, curiosity, enthusiasm, responsibility, tolerance, hard work, democratic, friendly / communicative, independent, religious, caring for the environment, and socially concerned. Hopefully, further research can be carried out to improve abilities understanding’s student concepts in basic mathematics subjects.Keywords: lesson study, reflection, basic mathematics